Using flash cards to improve the vocabulary learning in the english language with students of 7th year of basic education at Manuel Esteban Godoy Ortega school of Nangora. Academic period 2013- 2014 - Macas Puglla, Beatriz Cesibel (2015)
This descriptive study investigated the use of flash cards in the improvement of the vocabulary learning with seventh year students at Manuel Esteban Godoy Ortega public school. An intervention plan with ten sessions was applied to improve the vocabulary. Researcher’s-made tests and questionnaires were designed and used to measure the six students’ progress. Additional instruments like observation sheets were also used in every session to know the students’ advance. The results indicated that the use of flash cards improved the vocabulary learning which was reflected in the noticeable increase of the post test scores and students’ progress during the intervention. The answers received from the two questionnaires also confirmed the enthusiasm and the positive attitude toward working with flash cards. It might be concluded that this study helped the students to improve their vocabulary, the researcher to practice her teachings skills and the community to have a well-prepared candidate teacher.